1998
DOI: 10.1002/(sici)1097-0142(19980101)82:1<176::aid-cncr22>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of telomerase activity in malignant pheochromocytoma

Abstract: The expression of telomerase activity in pheochromocytoma clearly suggests the malignant behavior of the component cells. Analysis of telomerase activity appears to be a powerful tool for the diagnosis of malignant pheochromocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Early studies reported telomerase overexpression in malignant pheochromocytomas (19)(20)(21)(22)(23), whereas TERT promoter mutations (24,25) and hypermethylation (26) were recently found in a few SDHx-deficient paragangliomas. The phenotypic assignment of ALT based on telomeric analysis of histological preparations remains limited to 2 discrepant studies reporting a prevalence of 4% (27) and 27% (28) of 75 and 22 PPGLs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies reported telomerase overexpression in malignant pheochromocytomas (19)(20)(21)(22)(23), whereas TERT promoter mutations (24,25) and hypermethylation (26) were recently found in a few SDHx-deficient paragangliomas. The phenotypic assignment of ALT based on telomeric analysis of histological preparations remains limited to 2 discrepant studies reporting a prevalence of 4% (27) and 27% (28) of 75 and 22 PPGLs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a relatively reliable prediction of the malignant behavior of the pheochromocytoma has been presented. 6,7 However, the number of patients examined is not enough to draw a definite conclusion. Only careful follow up will give an answer as to whether this case is another primary paraganglioma in a setting of multiplicity or a metastatic one.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the normal adrenal medullae or the benign pheochromocytomas showed no telomerase activity. 47 Telomerase is a ribonucleoprotein complex including the telomerase RNA component, the telomeraseassociated protein (TP1), the telomerase catalytic subunit (hTERT) and the heat shock protein 90 (HSP90). In one study, the telomerase RNA component was found in 100% of malignant (9/9) and in 46% (13/28) of benign pheochromacytomas; 100% of malignant (9/9), but only 7% of benign (2/28) pheochromacytomas expressed hTERT; and HSP90 was increased in malignant pheochromacytomas, expressed at a lower level in benign pheochromacytomas.…”
Section: Molecular Markers Studiesmentioning
confidence: 99%